Sistem Evaluasi Pembelajaran dan Manajemen Perguruan Tinggi Berbasis E-Questionare - Ningrum, Sulistyo; Hariono, Tholib; Sufaidah, Siti (Exact Papers in Compilation (EPiC), 2022)
An evaluation at a university in particular of the learning and management of universities is vital. Where a teacher’s performance evaluation by astudent is conducted with the purpose of improving and improving the kualises and the quality of learning.Whereas head evaluation by subordinates to improve university management to better and better aim. In this study the authors create a college evaluation system on Website at UNWAHA. The data from the questionnaire is analyzed using a descriptive statistical technique with result obtained from charts and thus making it easier for leaders to look at and evaluate. Keywords: Lecturer’s Performance Evaluation; Lecturer’s Satisfaction; Websites.